The Carer, the Combatant and the Clandestine: images of women in the First World War in War Illustrated magazine. Issue 4 (7th June 2018) - Rayner, Jonathan
ABSTRACT: This essay examines the representation of women in War Illustrated magazine. Images of female civilians in Europe are central to narratives of German atrocities, while depictions of British women engaging in new occupations are key to the propagation of concepts of national unity. Women engaged in front-line nursing occupy a fluctuating status as vulnerable, potential victims and valiant pseudo-combatants. Female endeavours are celebrated in certain gender-specific roles (e.g. nursing, recruitment and charity work), while other occupations (spying, uniformed service and engaging in combat), are represented in paradoxical terms as responsible and heroic, or dangerous, transgressive activities. Within the magazine, images of women reinforce specific propagandist discourses, giving prominence to yet also problematising women's contributions to the conflict.